The Apocryphal Legitimation of a “Solomonic” Dynasty in the Kǝbrä nägäśt – A Reappraisal - Piovanelli, Pierluigi (Aethiopica, 2013)
The present study constitutes an attempt to reevaluate the ideological function of the Kǝbrä nägäśt as an apocryphal production extolling the nobility and orthodoxy of early 14th-century “Solomonic” élites. In this regard, the Kǝbrä nägäśt can be considered as the Ethiopian response to the religious and political propaganda of the Syriac Apocalypse of Pseudo-Methodius and related literature. The arguments recently made in favour of a 6th-century date for an hypothetical original kernel of the Kǝbrä nägäśt are also reexamined and reinterpreted. The mention of the “glory of David” in the inscription RIÉ 195 II: 24 is not a reference to the Davidic/Solomonic origins of the kings of Aksum but part of a biblical citation, Isaiah 22:22–23, here for the first time correctly identified, while the connection between the recently published MḤDYS’s gold coin and the council of Chalcedon is too speculative and aleatory to be of any use. The glorious memories of 6th-century Ḥimyaritic wars provided but the point of departure for the elaboration of the traditions to be much later creatively recycled in the Kǝbrä nägäśt.